Coating composition and method for preparing the same

By using coating compositions with components such as multifunctional epoxy resin and graphene dispersion, the problems of existing coatings being difficult to construct and poor media resistance in closed spaces are solved, and the rapid curing and high-performance anti-corrosion effect of the coating is achieved.

CN119799132AActive Publication Date: 2025-04-11PETROCHINA CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311300001.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-09
Publication Date
2025-04-11
Estimated Expiration
2043-10-09

AI Technical Summary

Technical Problem

The existing coating compositions are difficult to construct in closed spaces, have long drying and curing time, and have poor corrosion resistance and mechanical properties, making it difficult to meet the requirements of rapid construction and media resistance.

Method used

The coating composition consisting of phenol phenolic epoxy resin, bisphenol A type phenolic epoxy resin, glass flakes, graphene dispersion, phenoamine curing agent and alicyclic amine curing agent is used to improve the cross-linking density and medium resistance of the coating through the use of multifunctional epoxy resin, and the graphene dispersion is used to improve the heat resistance and corrosion resistance of the coating.

Benefits of technology

It realizes rapid drying and curing of the coating, improves mechanical properties and corrosion resistance, is suitable for high-temperature and high-pressure environments and acidic harsh environments, and meets the requirements of rapid construction and media resistance in closed spaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004484413010000071
    Figure BDA0004484413010000071
  • Figure BDA0004484413010000081
    Figure BDA0004484413010000081
  • Figure BDA0004484413010000091
    Figure BDA0004484413010000091
Patent Text Reader

Abstract

The invention provides a coating composition and a method for preparing the same. The coating composition is formed by a first composition and a second composition, wherein the first composition comprises the following components: phenol novolac epoxy resin, bisphenol A novolac epoxy resin, glass flakes, a graphene dispersion, other pigments and fillers, a first solvent, a reactive diluent, a thixotropic agent, a defoaming agent, a dispersing agent, a leveling agent and a base material wetting agent; and the second composition comprises the following components: a phenolic aldehyde amine curing agent, an alicyclic amine curing agent, a curing accelerator and a second solvent. The coating composition provided by the invention realizes the technical effects of improved corrosion resistance and mechanical properties, and rapid drying and curing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of anti-corrosion coatings, and in particular to a coating composition and a method for preparing the same. Background Art

[0002] Due to the small space and poor air circulation in closed spaces such as containers, oil tanks, and cabins, the equipment anti-corrosion process is prone to problems such as difficulty in construction, missing coatings, and poor construction quality. Due to the short construction time, it is difficult to ensure that the coating is well cured during the construction process. At the same time, due to the high corrosiveness of the storage medium, the inner wall anti-corrosion coating needs to have good medium resistance and mechanical properties.

[0003] Conventional epoxy coatings have good media resistance, but the coating takes a long time to dry and solidify, which does not meet the requirements of rapid construction and affects the progress of construction. Phenolic epoxy coatings have the characteristics of functionality>2 and heat resistance, fast reaction speed and high cross-linking density, but the mechanical properties of the coating such as flexibility and adhesion cannot meet the requirements, making it difficult to achieve good corrosion protection in harsh acidic environments.

[0004] Therefore, developing coatings with good physical and mechanical properties, resistance to corrosive media such as acids and alkalis, and rapid curing has become a research focus for solving the problem of corrosion protection in closed spaces and achieving rapid curing and media resistance.

[0005] In view of the above problems, it is necessary to develop a coating composition having improved anti-corrosion performance and mechanical properties and capable of rapid drying and curing, and a method for preparing the same. Summary of the invention

[0006] The main purpose of the present invention is to provide a coating composition and a method for preparing the same, so as to solve the problems of the coating composition in the prior art having a long drying and curing time or poor anti-corrosion performance and mechanical properties.

[0007] In order to achieve the above-mentioned purpose, the present invention provides a coating composition on the one hand, characterized in that the coating composition is formed by a first composition and a second composition, the first composition comprising the following components: phenol novolac epoxy resin, bisphenol A novolac epoxy resin, glass flakes, graphene dispersion, other pigments and fillers, a first solvent, an active diluent, a thixotropic agent, a defoaming agent, a dispersant, a leveling agent, and a substrate wetting agent; the second composition comprising the following components: a phenolic amine curing agent, an alicyclic amine curing agent, a curing accelerator, and a second solvent.

[0008] Furthermore, the first composition comprises the following components in parts by weight: 1 to 1.05 parts of phenol novolac epoxy resin, 1 to 1.2 parts of bisphenol A novolac epoxy resin, 1 to 1.13 parts of glass flakes, 0.03 to 0.05 parts of graphene dispersion, 1.53 to 1.61 parts of other pigments and fillers, 0.35 to 0.55 parts of a first solvent, 0.08 to 0.15 parts of a reactive diluent, and 0.01 to 0.0 3 parts, defoaming agent 0.012-0.018 parts, dispersant 0.006-0.008 parts, leveling agent 0.007-0.011 parts, substrate wetting agent 0.004-0.009 parts; the second composition comprises the following components in parts by weight: 3-3.1 parts of phenolic amine curing agent, 3.1-3.4 parts of alicyclic amine curing agent, 0.5-0.7 parts of curing accelerator, and 0.50-0.65 parts of the second solvent.

[0009] Furthermore, the phenol novolac epoxy resin is NPPN-631 phenol novolac epoxy resin, the bisphenol A novolac epoxy resin is F51 bisphenol A novolac epoxy resin; the glass flakes are glass flakes with a diameter of 60 to 80 mesh and a thickness of less than 7 μm; the graphene dispersion is a GRF-FLGOD-04 thin-layer graphene dispersion slurry; the other pigments and fillers include the following components in parts by weight: 0.45 to 0.59 parts of precipitated barium sulfate, 0.37 to 0.45 parts of rutile titanium dioxide, 0.11 to 0.18 parts of colloidal graphite, 0.27 to 0.38 parts of barite, 0.16 to 0.19 parts of ZP-01 composite modified zinc aluminum phosphate and 0.01 to 0.07 parts of nano silicon dioxide; the first solvent includes in parts by weight The invention discloses a novel solvent comprising the following components in parts by weight: 0.2275 to 0.3575 parts of xylene, 0.098 to 0.154 parts of n-butanol, and 0.0245 to 0.0385 parts of ethyl acetate; the second solvent comprises the following components in parts by weight: 0.325 to 0.4225 parts of xylene, 0.14 to 0.182 parts of n-butanol, and 0.035 to 0.0455 parts of ethyl acetate; the active diluent is 1,6-hexanediol diglycidyl ether; the thixotropic agent is polyamide wax, the defoamer is CK021 type polyether ester defoamer, the dispersant is BYK-163 type high molecular weight block copolymer dispersant containing affinity groups, the leveling agent is BYK-320 type polyether modified methane polysiloxane copolymer leveling agent, and the substrate wetting agent is TEGO Wet 270 type polyether siloxane copolymer wetting agent; the phenolic amine curing agent is DF1228 type cardanol modified phenolic amine curing agent, the alicyclic amine curing agent is Ancamine 2636 modified fatty amine curing agent, and the curing accelerator is DMP-30 type curing agent.

[0010] Furthermore, the weight ratio of the first composition to the second composition is 1:0.21-0.25, preferably 1:0.22-0.23.

[0011] In order to achieve the above object, another aspect of the present invention also provides a method for preparing the above coating composition, comprising the following steps:

[0012] 1) mixing and stirring the components of the first composition except the glass flakes and the graphene dispersion to obtain a coating mixture;

[0013] 2) grinding the coating mixture obtained in step 1) to obtain a coating base liquid;

[0014] 3) adding the glass flakes and the graphene dispersion into the coating base liquid and stirring to obtain the first composition;

[0015] 4) mixing and stirring the components of the second composition to obtain the second composition;

[0016] 5) Mixing the first composition and the second composition to obtain the coating composition.

[0017] Furthermore, in step 1), the bisphenol A novolac epoxy resin physically modifies the phenol novolac epoxy resin.

[0018] Further, step 1) comprises the following steps:

[0019] i) mixing the phenol novolac epoxy resin, the bisphenol A novolac epoxy resin, the reactive diluent and the first solvent and performing a first stirring to obtain a resin solution, wherein the first stirring temperature is ≤50° C., the rotation speed is 2000-2500 r / min, and the time is 20-25 min;

[0020] ii) adding the defoamer, the dispersant, the leveling agent, and the substrate wetting agent into the resin solution and performing a second stirring to obtain a resin mixed solution, wherein the second stirring temperature is ≤40° C., the rotation speed is 1000-1500 r / min, and the time is 5-10 min;

[0021] iii) adding the thixotropic agent and the other pigments and fillers into the resin mixed solution and performing a third stirring, wherein the third stirring temperature is ≤50° C., the rotation speed is 2000-2500 r / min, and the time is 25-30 min.

[0022] Furthermore, the grinding in step 2) is carried out for 1 to 1.5 hours, and the grinding fineness is ≤ 60 μm.

[0023] Furthermore, the stirring temperature in step 3) is ≤60°C, the rotation speed is 2000-2500 r / min, and the time is 30-40 min; the stirring temperature in step 4) is ≤30°C, the rotation speed is 1000-1500 r / min, and the time is 15-20 min.

[0024] By applying the technical scheme of the present invention, the fast-curing coating of the present invention has good mechanical properties, corrosion resistance and fast drying and curing properties. Phenol novolac epoxy resin and bisphenol A novolac epoxy resin are used as film-forming resins, and the cross-linking density of the coating is improved with phenolic amine curing agent and alicyclic amine curing agent, and the medium resistance and heat resistance of the system are improved by using multifunctional epoxy resin. The two phenolic epoxy resins are mixed to promote the coating to quickly induce the cross-linking reaction of the coating at different ambient temperatures, thereby achieving rapid curing of the coating. The use of graphene dispersions to improve the stability and dispersibility of graphene in the coating can effectively improve the use effect of graphene. Introducing graphene into the coating can improve the heat resistance, medium resistance, and salt spray resistance of the coating, and extend the H + , HS - 、SO4 2- , Cl - The corrosive ion penetration path forms a soft and hard flaky system with glass flakes, effectively improving the anti-corrosion effect of the coating. The use of active diluents can reduce the viscosity of the coating while increasing the cross-linking density of the resin and curing agent. DETAILED DESCRIPTION

[0025] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0026] As described in the background art, the coating compositions in the prior art have the problems of long drying and curing time or poor anti-corrosion and mechanical properties. In order to solve the above technical problems, the present application provides a coating composition, which is formed by a first composition and a second composition, wherein the first composition comprises the following components: phenol novolac epoxy resin, bisphenol A novolac epoxy resin, glass flakes, graphene dispersion, other pigments and fillers, a first solvent, a reactive diluent, a thixotropic agent, a defoaming agent, a dispersant, a leveling agent, and a substrate wetting agent; the second composition comprises the following components: a phenolic amine curing agent, an alicyclic amine curing agent, a curing accelerator, and a second solvent.

[0027] The fast-curing coating of the present invention has good mechanical properties, corrosion resistance and fast drying and curing properties. Phenol novolac epoxy resin and bisphenol A novolac epoxy resin are used as film-forming resins, and the cross-linking density of the coating is improved with phenolic amine curing agent and alicyclic amine curing agent, and the medium resistance and heat resistance of the system are improved by using multifunctional epoxy resin. The two phenolic epoxy resins are mixed to promote the coating to quickly induce the cross-linking reaction of the coating at different ambient temperatures, thereby achieving rapid curing of the coating. The use of graphene dispersions to improve the stability and dispersibility of graphene in the coating can effectively improve the use effect of graphene. Introducing graphene into the coating can improve the heat resistance, medium resistance, and salt spray resistance of the coating, and extend the H + , HS - 、SO4 2- , Cl - The corrosive ion penetration path forms a soft and hard flaky system with glass flakes, effectively improving the anti-corrosion effect of the coating. The use of active diluents can reduce the viscosity of the coating while increasing the cross-linking density of the resin and curing agent.

[0028] The coating composition of the present invention can be used in working medium environments containing strong acid corrosion such as H2S, CO2, H2SO4, HCl, etc., can be used in high temperature and high pressure environments with temperatures up to 100°C and pressures of 30MPa, can be used for long-term inner wall corrosion protection of the surfaces of high temperature and high pressure equipment such as pressure vessels, oil tanks, sewage tanks, oil-water separators, etc. that contact the medium, and can achieve rapid curing and rapid construction of the coating.

[0029] In a preferred embodiment, the first composition comprises the following components in parts by weight: 1-1.05 parts of phenol novolac epoxy resin, 1-1.2 parts of bisphenol A novolac epoxy resin, 1-1.13 parts of glass flakes, 0.03-0.05 parts of graphene dispersion, 1.53-1.61 parts of other pigments and fillers, 0.35-0.55 parts of the first solvent, 0.08-0.15 parts of the active diluent, and 0.01-0.15 parts of the thixotropic agent. 0.03 parts, defoaming agent 0.012-0.018 parts, dispersant 0.006-0.008 parts, leveling agent 0.007-0.011 parts, substrate wetting agent 0.004-0.009 parts; the second composition comprises the following components in parts by weight: 3-3.1 parts of phenolic amine curing agent, 3.1-3.4 parts of alicyclic amine curing agent, 0.5-0.7 parts of curing accelerator, and 0.50-0.65 parts of the second solvent.

[0030] In a preferred embodiment, the first composition comprises the following components in parts by weight: 1 part of phenol novolac epoxy resin, 1 part of bisphenol A novolac epoxy resin, 1.05 parts of glass flakes, 0.05 parts of graphene dispersion, 1.54 parts of other pigments and fillers, 0.35 parts of a first solvent, 0.1 parts of an active diluent, 0.01 parts of a thixotropic agent, 0.015 parts of a defoaming agent, 0.008 parts of a dispersant, 0.011 parts of a leveling agent, and 0.005 parts of a substrate wetting agent; the second composition comprises the following components in parts by weight: 3 parts of a phenolic amine curing agent, 3.1 parts of alicyclic amine curing agent, 0.7 parts of a curing accelerator, and 0.51 parts of a second solvent.

[0031] The use of the components within the specific content range of the present invention to form a coating composition is conducive to forming a coating composition with further improved mechanical properties, corrosion resistance and drying and curing time. When the specific content range of the present invention is exceeded, differences in the solid content, pigment-to-base ratio, etc. of the coating system will lead to different film thickness and coating coverage, resulting in relatively reduced coating adhesion, media resistance, and workability.

[0032] In a preferred embodiment, the phenol novolac epoxy resin is NPPN-631 phenol novolac epoxy resin, the bisphenol A novolac epoxy resin is F51 bisphenol A novolac epoxy resin; the glass flakes are glass flakes with a sheet diameter of 60 to 80 mesh and a thickness of less than 7 μm; the graphene dispersion is a GRF-FLGOD-04 thin-layer graphene dispersion slurry; the other pigments and fillers include the following components in parts by weight: 0.45 to 0.59 parts of precipitated barium sulfate, 0.37 to 0.45 parts of rutile titanium dioxide, 0.11 to 0.18 parts of colloidal graphite, 0.27 to 0.38 parts of barite, and 0.16 to 0.19 parts of ZP-01 composite modified zinc aluminum phosphate (ZP-01 composite modified zinc aluminum phosphate from Noelson Chemical, model number NOELSON ZP-01 type zinc aluminum phosphate) and 0.01-0.07 parts of nano silicon dioxide; the first solvent comprises the following components by weight: 0.2275-0.3575 parts of xylene, 0.098-0.154 parts of n-butanol, 0.0245-0.0385 parts of ethyl acetate, the second solvent comprises the following components by weight: 0.325-0.4225 parts of xylene, 0.14-0.182 parts of n-butanol, 0.035 to 0.0455 parts of ethyl acetate; the active diluent is 1,6-hexanediol diglycidyl ether; the thixotropic agent is polyamide wax, the defoamer is CK021 type polyether ester defoamer, the dispersant is BYK-163 type high molecular weight block copolymer dispersant containing affinity groups, the leveling agent is BYK-320 type polyether modified methane polysiloxane copolymer leveling agent, the substrate wetting agent is TEGO Wet 270 type polyether siloxane copolymer wetting agent; the phenolic amine curing agent is DF1228 type cardanol modified phenolic amine curing agent, the alicyclic amine curing agent is Ancamine 2636 modified fatty amine curing agent, and the curing accelerator is DMP-30 type curing agent.

[0033] The specific components of the present invention are used to form a coating composition, which is conducive to forming a coating composition with further improved mechanical properties, corrosion resistance and drying and curing time. In which, zinc aluminum phosphate is used as a filler, and zinc aluminum phosphate has the rust-proof effect of both zinc phosphate and aluminum phosphate. 3+ The addition of ions increases the phosphate ion and Fe 3+ The chelation of ions realizes the passivation film system of electrochemical corrosion protection and physical isolation corrosion protection, and improves the medium resistance and adhesion of the system. 1,6-hexanediol diglycidyl ether is used as an active diluent. 1,6-hexanediol diglycidyl ether is linear and has a diepoxy group. It can be matched with multifunctional epoxy resin to achieve effective grading, forming interpenetration of high molecular weight and low molecular weight film-forming materials, and improving the film-forming crosslinking density of the system.

[0034] In a preferred embodiment, the weight ratio of the first composition to the second composition is 1:0.21-0.25, preferably 1:0.22-0.23.

[0035] The use of the weight ratio of the first composition to the second composition of the present invention to form a coating composition is conducive to forming a coating composition with further improved mechanical properties, corrosion resistance and drying and curing time. When the weight ratio of the first composition to the second composition is exceeded, the curability and corrosion resistance of the coating will be relatively reduced.

[0036] In a preferred embodiment, the coating composition has an adhesion of ≥20 MPa, is resistant to saturated H2S aqueous solution for 1000 h at room temperature, remains intact for 24 h in a high temperature and high pressure test at a temperature of 80°C, a pressure of 30 MPa, and a pH of 12.5, remains intact for 1000 h in a 30% H2SO4 solution, a 12% HCl+3% HF solution, a 20% H3PO3 solution, or a 20% NaOH solution at 70°C, and has a chloride ion permeability resistance of ≥1.2×10 -3 mg / (cm 2 ·d), flexibility 1mm coating is intact.

[0037] In a preferred embodiment, the coating composition has a surface drying time of ≤1 h at 25°C, a through drying time of ≤4 h, and a coating curing time of ≤4 d.

[0038] Another aspect of the present application provides a method for preparing the above-mentioned coating composition, comprising the following steps:

[0039] 1) mixing and stirring the components of the first composition except the glass flakes and the graphene dispersion to obtain a coating mixture;

[0040] 2) grinding the coating mixture obtained in step 1) to obtain a coating base liquid;

[0041] 3) adding the glass flakes and the graphene dispersion into the coating base liquid and stirring to obtain the first composition;

[0042] 4) mixing and stirring the components of the second composition to obtain the second composition;

[0043] 5) Mixing the first composition and the second composition to obtain the coating composition.

[0044] The preparation method of the present invention can form a coating composition with improved mechanical properties, corrosion resistance and drying and curing time. Grinding the coating mixture can further disperse the liquid and powder raw materials and achieve a certain fineness. Glass flakes and graphene dispersions are special functional fillers, which can only play a role when their diameter-thickness ratio is large. Grinding will destroy their diameter-thickness ratio, so they are not suitable for the grinding process.

[0045] In a preferred embodiment, in step 1), the bisphenol A novolac epoxy resin physically modifies the phenol novolac epoxy resin.

[0046] The phenol novolac epoxy resin is physically modified by using bisphenol A novolac epoxy resin to achieve the combination of the two resins, which can improve the media resistance of the phenol novolac epoxy resin.

[0047] In a preferred embodiment, step 1) comprises the following steps:

[0048] i) mixing the phenol novolac epoxy resin, the bisphenol A novolac epoxy resin, the reactive diluent and the first solvent and performing a first stirring to obtain a resin solution, wherein the first stirring temperature is ≤50° C., the rotation speed is 2000-2500 r / min, and the time is 20-25 min;

[0049] ii) adding the defoamer, the dispersant, the leveling agent, and the substrate wetting agent into the resin solution and performing a second stirring to obtain a resin mixed solution, wherein the second stirring temperature is ≤40° C., the rotation speed is 1000-1500 r / min, and the time is 5-10 min;

[0050] iii) adding the thixotropic agent and the other pigments and fillers into the resin mixed solution and performing a third stirring, wherein the third stirring temperature is ≤50° C., the rotation speed is 2000-2500 r / min, and the time is 25-30 min.

[0051] Mixing the components separately in multiple mixing steps and dispersing the components that require different dispersion speeds and sequences separately are more conducive to obtaining a well-mixed coating mixture.

[0052] In a preferred embodiment, the grinding in step 2) is performed for 1 to 1.5 hours, and the grinding fineness is ≤ 60 μm.

[0053] The first composition is prepared using the specific steps and parameters of the present invention, which can form a coating composition with improved mechanical properties, corrosion resistance and drying and curing time. Exceeding the above stirring and grinding parameter ranges may result in a relative decrease in coating uniformity and coating viscosity, resulting in a relative decrease in coating quality.

[0054] In a preferred embodiment, the stirring temperature in step 3) is ≤60°C, the rotation speed is 2000-2500 r / min, and the time is 30-40 min; the stirring temperature in step 4) is ≤30°C, the rotation speed is 1000-1500 r / min, and the time is 15-20 min.

[0055] The specific steps and parameters of the present invention are used to prepare the second composition, which can form a coating composition with improved mechanical properties, corrosion resistance and drying and curing time. Exceeding the above stirring parameter range may result in a relative decrease in coating uniformity and coating viscosity, and may also result in a change in coating thixotropy that affects the construction thickness of the coating, resulting in a relative decrease in coating construction performance and quality.

[0056] In a preferred embodiment, the method for preparing the coating composition comprises the following steps:

[0057] 1) adding phenolic epoxy resin B, mixed solvent and active diluent to phenolic epoxy resin A, stirring once to make the components dispersed evenly, cooling to room temperature to obtain phenolic epoxy resin liquid, wherein the stirring temperature is ≤50°C, the rotation speed is 2000-2500r / min, and the time is 20-25min;

[0058] 2) Add defoamer, dispersant, leveling agent and substrate wetting agent to the resin solution, perform secondary stirring to evenly disperse the components, and obtain a resin mixed solution. The secondary stirring temperature is ≤40°C, the rotation speed is 1000-1500r / min, and the time is 5-10min;

[0059] 3) Adding thixotropic agent, precipitated barium sulfate, rutile titanium dioxide, colloidal graphite, barite, ZP-01 composite modified zinc aluminum phosphate and nano-silicon dioxide to the mixed solution, stirring three times to make the components dispersed evenly, to obtain a coating mixture, the temperature of the three stirrings is ≤50°C, the speed is 2000-2500r / min, and the time is 25-30min;

[0060] 4) grinding the coating mixture obtained in step 3) with a sand mill for 1 to 1.5 hours to obtain a coating base liquid, with a grinding fineness of ≤60 μm;

[0061] 5) adding the glass flakes and the graphene dispersion to the coating base liquid obtained in step 4), stirring four times to evenly disperse the components to obtain a first composition, wherein the temperature of the four stirrings is ≤60°C, the rotation speed is 2000-2500 r / min, and the time is 30-40 min;

[0062] 6) adding a phenolic amine curing agent, an alicyclic amine curing agent, and a curing accelerator to a mixed solvent, stirring for five times to uniformly disperse the components, and obtaining a second composition, wherein the five stirrings are performed at a temperature of ≤30° C., a rotation speed of 1000 to 1500 r / min, and a time of 15 to 20 min;

[0063] 7) The first composition and the second composition are mixed uniformly to obtain a coating composition.

[0064] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0065] The coating composition was prepared by the following examples. The parts of each component in the examples are parts by weight. There is no specific requirement for the reagents used in the examples, and commercially available reagents can be used.

[0066] Example 1

[0067] 1) Add 1 part of F51 bisphenol A novolac epoxy resin, 0.2275 parts of xylene, 0.098 parts of n-butanol, 0.0245 parts of ethyl acetate, and 0.1 parts of 1,6-hexanediol diglycidyl ether to 1 part of NPPN-631 phenol novolac epoxy resin, stir at 2000 r / min for 25 minutes, and control the temperature below 50° C.;

[0068] 2) adding 0.015 parts of CK021 polyether ester defoamer, 0.008 parts of BYK-163 high molecular weight block copolymer dispersant containing affinity groups, 0.011 parts of BYK-320 polyether modified methane polysiloxane copolymer leveling agent, and 0.005 parts of TEGOWet270 polyether siloxane copolymer wetting agent to the solution obtained in step 1), stirring at a low speed of 1000 r / min for 5 minutes, and controlling the stirring temperature to be lower than 40° C.;

[0069] 3) adding 0.01 parts of polyamide wax, 0.45 parts of precipitated barium sulfate, 0.38 parts of rutile titanium dioxide, 0.11 parts of colloidal graphite, 0.29 parts of barite, 0.18 parts of ZP-01 composite modified zinc aluminum phosphate, and 0.02 parts of nano-silicon dioxide to the solution obtained in step 2), and stirring at 2500 r / min for 30 minutes, controlling the stirring temperature to be lower than 50° C.;

[0070] 4) Grinding the solution obtained in step 3) with a sand mill for 1.0 h to obtain a coating base liquid, with the grinding fineness being controlled to be ≤60 μm;

[0071] 5) adding 1.05 parts of glass flakes with a diameter of 60 to 80 meshes and 0.05 parts of GRF-FLGOD-04 thin-layer graphene dispersion slurry to the coating base liquid obtained in step 4), stirring at 2000 r / min for 40 minutes, controlling the stirring temperature to be lower than 60° C., to obtain a first composition;

[0072] 6) adding 3 parts of DF1228 cardanol modified phenolic amine curing agent, 3.1 parts of Ancamine 2636 modified fatty amine curing agent, and 0.7 parts of DMP-30 curing agent to 0.3315 parts of xylene, 0.1428 parts of n-butanol, and 0.037 parts of ethyl acetate, stirring at 1500 r / min for 20 minutes, and controlling the stirring temperature to be lower than 30° C. to obtain a second composition;

[0073] 7) The component A and the component B are mixed uniformly in a weight ratio of 1:0.23 to obtain a coating composition.

[0074] The properties of the coating composition prepared in Example 1 were tested, and the results are shown in Table 1.

[0075] Table 1 Properties of the coating composition prepared in Example 1

[0076]

[0077]

[0078] Example 2

[0079] 1) Add 1.2 parts of F51 bisphenol A novolac epoxy resin, 0.3575 parts of xylene, 0.154 parts of n-butanol, 0.0385 parts of ethyl acetate, and 0.11 parts of 1,6-hexanediol diglycidyl ether to 1 part of NPPN-631 phenol novolac epoxy resin, stir at 2500 r / min for 20 minutes, and control the temperature below 50° C.;

[0080] 2) adding 0.013 parts of CK021 polyether ester defoamer, 0.008 parts of BYK-163 high molecular weight block copolymer dispersant containing affinity groups, 0.010 parts of BYK-320 polyether modified methane polysiloxane copolymer leveling agent, and 0.008 parts of TEGOWet270 polyether siloxane copolymer wetting agent to the solution obtained in step 1), stirring at a low speed of 1000 r / min for 10 minutes, and controlling the stirring temperature to be lower than 40° C.;

[0081] 3) adding 0.02 parts of polyamide wax, 0.58 parts of precipitated barium sulfate, 0.45 parts of rutile titanium dioxide, 0.18 parts of colloidal graphite, 0.38 parts of barite, 0.17 parts of ZP-01 composite modified zinc aluminum phosphate, and 0.07 parts of nano-silicon dioxide to the solution obtained in step 2), and stirring at 2000 r / min for 30 minutes, controlling the stirring temperature to be lower than 50° C.;

[0082] 4) Grinding the solution obtained in step 3) with a sand mill for 1.5 hours to obtain a coating base liquid, with the grinding fineness being controlled to be ≤60 μm;

[0083] 5) adding 1.13 parts of glass flakes with a diameter of 60 to 80 meshes and 0.03 parts of GRF-FLGOD-04 thin-layer graphene dispersion slurry to the coating base liquid obtained in step 4), stirring at 2300 r / min for 35 minutes, controlling the stirring temperature to be lower than 60° C., to obtain a first composition;

[0084] 6) adding 3 parts of DF1228 cardanol modified phenolic amine curing agent, 3.4 parts of Ancamine 2636 modified fatty amine curing agent, and 0.5 parts of DMP-30 curing agent to 0.4225 parts of xylene, 0.182 parts of n-butanol, and 0.0455 parts of ethyl acetate, stirring at 1500 r / min for 15 minutes, and controlling the stirring temperature to be lower than 30° C. to obtain a second composition;

[0085] 7) The first composition and the second composition are mixed uniformly in a weight ratio of 1:0.24 to obtain a coating composition.

[0086] The properties of the coating composition prepared in Example 2 were tested, and the results are shown in Table 2.

[0087] Table 2 Properties of the coating composition prepared in Example 2

[0088]

[0089] Example 3

[0090] 1) Add 1.1 parts of F51 bisphenol A novolac epoxy resin, 0.26 parts of xylene, 0.112 parts of n-butanol, 0.028 parts of ethyl acetate, and 0.08 parts of 1,6-hexanediol diglycidyl ether to 1 part of NPPN-631 phenol novolac epoxy resin, stir at 2200 r / min for 23 minutes, and control the temperature below 50° C.;

[0091] 2) adding 0.015 parts of CK021 polyether ester defoamer, 0.006 parts of BYK-163 high molecular weight block copolymer dispersant containing affinity groups, 0.007 parts of BYK-320 polyether modified methane polysiloxane copolymer leveling agent, and 0.005 parts of TEGOWet270 polyether siloxane copolymer wetting agent to the solution obtained in step 1), stirring at a low speed of 1500 r / min for 5 minutes, and controlling the stirring temperature to be lower than 40° C.;

[0092] 3) adding 0.02 parts of polyamide wax, 0.46 parts of precipitated barium sulfate, 0.41 parts of rutile titanium dioxide, 0.14 parts of colloidal graphite, 0.27 parts of barite, 0.19 parts of ZP-01 composite modified zinc aluminum phosphate, and 0.01 parts of nano-silicon dioxide to the solution obtained in step 2), and stirring at 2200 r / min for 28 minutes, controlling the stirring temperature to be lower than 50° C.;

[0093] 4) Grinding the solution obtained in 3) with a sand mill for 1.0 h to obtain a coating base liquid, with the grinding fineness controlled to be ≤60 μm;

[0094] 5) adding 1.03 parts of glass flakes with a diameter of 60 to 80 meshes and 0.04 parts of GRF-FLGOD-04 thin-layer graphene dispersion slurry to the coating base liquid obtained in step 4), stirring at 2100 r / min for 38 minutes, controlling the stirring temperature to be lower than 60° C., to obtain a first composition;

[0095] 6) adding 3 parts of DF1228 cardanol modified phenolic amine curing agent, 3.4 parts of Ancamine 2636 modified fatty amine curing agent, and 0.7 parts of DMP-30 curing agent to 0.39 parts of xylene, 0.168 parts of n-butanol, and 0.042 parts of ethyl acetate, stirring at 1300 r / min for 18 minutes, and controlling the stirring temperature to be lower than 30° C. to obtain a second composition;

[0096] 7) The first composition and the second composition are mixed in a weight ratio of 1:0.21 to obtain a coating composition.

[0097] The properties of the coating composition prepared in Example 3 were tested, and the results are shown in Table 3.

[0098] Table 3 Properties of the coating composition prepared in Example 3

[0099]

[0100] Example 4

[0101] 1) Add 1.2 parts of F51 bisphenol A novolac epoxy resin, 0.247 parts of xylene, 0.1064 parts of n-butanol, 0.0266 parts of ethyl acetate, and 0.12 parts of 1,6-hexanediol diglycidyl ether to 1 part of NPPN-631 phenol novolac epoxy resin, stir at 2100 r / min for 21 minutes, and control the temperature below 50° C.;

[0102] 2) adding 0.018 parts of CK021 polyether ester defoamer, 0.007 parts of BYK-163 high molecular weight block copolymer dispersant containing affinity groups, 0.01 parts of BYK-320 polyether modified methane polysiloxane copolymer leveling agent, and 0.006 parts of TEGOWet270 polyether siloxane copolymer wetting agent to the solution obtained in step 1), stirring at a low speed of 1200 r / min for 8 minutes, and controlling the stirring temperature to be lower than 40° C.;

[0103] 3) adding 0.02 parts of polyamide wax, 0.52 parts of precipitated barium sulfate, 0.38 parts of rutile titanium dioxide, 0.15 parts of colloidal graphite, 0.31 parts of barite, 0.18 parts of ZP-01 composite modified zinc aluminum phosphate, and 0.02 parts of nano-silicon dioxide to the solution obtained in step 2), and stirring at 2300 r / min for 30 minutes, controlling the stirring temperature to be lower than 50° C.;

[0104] 4) Grinding the solution obtained in 3) with a sand mill for 1.3 hours to obtain a coating base liquid, with the grinding fineness controlled to be ≤60 μm;

[0105] 5) adding 1.12 parts of glass flakes with a diameter of 60 to 80 meshes and 0.03 parts of GRF-FLGOD-04 thin-layer graphene dispersion slurry to the coating base liquid obtained in step 4), stirring at 2300 r / min for 35 minutes, controlling the stirring temperature to be lower than 60° C., to obtain a first composition;

[0106] 6) adding 3 parts of DF1228 cardanol modified phenolic amine curing agent, 3.2 parts of Ancamine 2636 modified fatty amine curing agent, and 0.6 parts of DMP-30 curing agent to 0.3575 parts of xylene, 0.154 parts of n-butanol, and 0.0385 parts of ethyl acetate, stirring at 1400 r / min for 19 minutes, and controlling the stirring temperature to be lower than 30° C. to obtain a second composition;

[0107] 7) The first composition and the second composition are mixed uniformly at a weight ratio of 1:0.25 to obtain a coating composition.

[0108] The properties of the coating composition prepared in Example 4 were tested, and the results are shown in Table 4.

[0109] Table 4 Properties of the coating composition prepared in Example 4

[0110]

[0111]

[0112] Comparative Example 1

[0113] Comparative Example 1 is different in that Comparative Example 1 does not contain bisphenol A novolac epoxy resin.

[0114] 1) Add 0.2275 parts of xylene, 0.098 parts of n-butanol, 0.0245 parts of ethyl acetate, and 0.1 parts of 1,6-hexanediol diglycidyl ether to 1 part of NPPN-631 phenol novolac epoxy resin, stir at 2000 r / min for 25 minutes, and control the temperature below 50°C;

[0115] 2) adding 0.015 parts of CK021 polyether ester defoamer, 0.008 parts of BYK-163 high molecular weight block copolymer dispersant containing affinity groups, 0.011 parts of BYK-320 polyether modified methane polysiloxane copolymer leveling agent, and 0.005 parts of TEGOWet270 polyether siloxane copolymer wetting agent to the solution obtained in step 1), stirring at a low speed of 1000 r / min for 5 minutes, and controlling the stirring temperature to be lower than 40° C.;

[0116] 3) adding 0.01 parts of polyamide wax, 0.45 parts of precipitated barium sulfate, 0.38 parts of rutile titanium dioxide, 0.11 parts of colloidal graphite, 0.29 parts of barite, 0.18 parts of ZP-01 composite modified zinc aluminum phosphate, and 0.02 parts of nano-silicon dioxide to the solution obtained in step 2), and stirring at 2500 r / min for 30 minutes, controlling the stirring temperature to be lower than 50° C.;

[0117] 4) Grinding the solution obtained in step 3) with a sand mill for 1.0 h to obtain a coating base liquid, with the grinding fineness being controlled to be ≤60 μm;

[0118] 5) adding 1.05 parts of glass flakes with a diameter of 60 to 80 meshes and 0.05 parts of GRF-FLGOD-04 thin-layer graphene dispersion slurry to the coating base liquid obtained in step 4), stirring at 2000 r / min for 40 minutes, controlling the stirring temperature to be lower than 60° C., to obtain a first composition;

[0119] 6) adding 3 parts of DF1228 cardanol modified phenolic amine curing agent, 3.1 parts of Ancamine 2636 modified fatty amine curing agent, and 0.7 parts of DMP-30 curing agent to 0.3315 parts of xylene, 0.1428 parts of n-butanol, and 0.037 parts of ethyl acetate, stirring at 1500 r / min for 20 minutes, and controlling the stirring temperature to be lower than 30° C. to obtain a second composition;

[0120] 7) The component A and the component B are mixed uniformly in a weight ratio of 1:0.08 to obtain a coating composition.

[0121] The properties of the coating composition prepared in Comparative Example 1 were tested, and the results are shown in Table 5.

[0122] Table 5 Properties of the coating composition prepared in Comparative Example 1

[0123]

[0124]

[0125] Comparative Example 2

[0126] Comparative Example 1 is different in that Comparative Example 2 does not contain the graphene dispersion.

[0127] 1) Add 1 part of F51 bisphenol A novolac epoxy resin, 0.2275 parts of xylene, 0.098 parts of n-butanol, 0.0245 parts of ethyl acetate, and 0.1 parts of 1,6-hexanediol diglycidyl ether to 1 part of NPPN-631 phenol novolac epoxy resin, stir at 2000 r / min for 25 minutes, and control the temperature below 50° C.;

[0128] 2) adding 0.015 parts of CK021 polyether ester defoamer, 0.008 parts of BYK-163 high molecular weight block copolymer dispersant containing affinity groups, 0.011 parts of BYK-320 polyether modified methane polysiloxane copolymer leveling agent, and 0.005 parts of TEGOWet270 polyether siloxane copolymer wetting agent to the solution obtained in step 1), stirring at a low speed of 1000 r / min for 5 minutes, and controlling the stirring temperature to be lower than 40° C.;

[0129] 3) adding 0.01 parts of polyamide wax, 0.45 parts of precipitated barium sulfate, 0.38 parts of rutile titanium dioxide, 0.11 parts of colloidal graphite, 0.29 parts of barite, 0.18 parts of ZP-01 composite modified zinc aluminum phosphate, and 0.02 parts of nano-silicon dioxide to the solution obtained in step 2), and stirring at 2500 r / min for 30 minutes, controlling the stirring temperature to be lower than 50° C.;

[0130] 4) Grinding the solution obtained in step 3) with a sand mill for 1.0 h to obtain a coating base liquid, with the grinding fineness being controlled to be ≤60 μm;

[0131] 5) adding 1.05 parts of glass flakes with a diameter of 60-80 meshes to the coating base liquid obtained in step 4), stirring at a high speed of 2000 r / min for 40 min, and controlling the stirring temperature to be lower than 60° C. to obtain a first composition;

[0132] 6) adding 3 parts of DF1228 cardanol modified phenolic amine curing agent, 3.1 parts of Ancamine 2636 modified fatty amine curing agent, and 0.7 parts of DMP-30 curing agent to 0.3315 parts of xylene, 0.1428 parts of n-butanol, and 0.037 parts of ethyl acetate, stirring at 1500 r / min for 20 minutes, and controlling the stirring temperature to be lower than 30° C. to obtain a second composition;

[0133] 7) The component A and the component B are mixed uniformly in a weight ratio of 1:0.23 to obtain a coating composition.

[0134] The properties of the coating composition prepared in Comparative Example 2 were tested, and the results are shown in Table 6.

[0135] Table 6 Properties of the coating composition prepared in Comparative Example 2

[0136]

[0137] Comparative Example 3

[0138] Comparative Example 1 is different in that Comparative Example 3 does not contain zinc aluminum phosphate.

[0139] 1) Add 1 part of F51 bisphenol A novolac epoxy resin, 0.2275 parts of xylene, 0.098 parts of n-butanol, 0.0245 parts of ethyl acetate, and 0.1 parts of 1,6-hexanediol diglycidyl ether to 1 part of NPPN-631 phenol novolac epoxy resin, stir at 2000 r / min for 25 minutes, and control the temperature below 50° C.;

[0140] 2) adding 0.015 parts of CK021 polyether ester defoamer, 0.008 parts of BYK-163 high molecular weight block copolymer dispersant containing affinity groups, 0.011 parts of BYK-320 polyether modified methane polysiloxane copolymer leveling agent, and 0.005 parts of TEGOWet270 polyether siloxane copolymer wetting agent to the solution obtained in step 1), stirring at a low speed of 1000 r / min for 5 minutes, and controlling the stirring temperature to be lower than 40° C.;

[0141] 3) adding 0.01 parts of polyamide wax, 0.45 parts of precipitated barium sulfate, 0.38 parts of rutile titanium dioxide, 0.11 parts of colloidal graphite, 0.29 parts of barite, and 0.02 parts of nano-silicon dioxide to the solution obtained in step 2), and stirring at 2500 r / min for 30 minutes, controlling the stirring temperature to be lower than 50° C.;

[0142] 4) Grinding the solution obtained in step 3) with a sand mill for 1.0 h to obtain a coating base liquid, with the grinding fineness being controlled to be ≤60 μm;

[0143] 5) adding 1.05 parts of glass flakes with a diameter of 60 to 80 meshes and 0.05 parts of GRF-FLGOD-04 thin-layer graphene dispersion slurry to the coating base liquid obtained in step 4), stirring at 2000 r / min for 40 minutes, controlling the stirring temperature to be lower than 60° C., to obtain a first composition;

[0144] 6) adding 3 parts of DF1228 cardanol modified phenolic amine curing agent, 3.1 parts of Ancamine 2636 modified fatty amine curing agent, and 0.7 parts of DMP-30 curing agent to 0.3315 parts of xylene, 0.1428 parts of n-butanol, and 0.037 parts of ethyl acetate, stirring at 1500 r / min for 20 minutes, and controlling the stirring temperature to be lower than 30° C. to obtain a second composition;

[0145] 7) The component A and the component B are mixed uniformly in a weight ratio of 1:0.23 to obtain a coating composition.

[0146] The properties of the coating composition prepared in Comparative Example 3 were tested, and the results are shown in Table 7.

[0147] Table 7 Properties of the coating composition prepared in Comparative Example 3

[0148]

[0149] Comparative Example 4

[0150] Comparative Example 1 is different in that the contents of some components in Comparative Example 4 are outside the preferred range defined in the present invention.

[0151] 1) Add 1.3 parts of F51 bisphenol A novolac epoxy resin, 0.2275 parts of xylene, 0.098 parts of n-butanol, 0.0245 parts of ethyl acetate, and 0.25 parts of 1,6-hexanediol diglycidyl ether to 1 part of NPPN-631 phenol novolac epoxy resin, stir at 2000 r / min for 25 minutes, and control the temperature to be below 50° C.;

[0152] 2) adding 0.010 parts of CK021 polyether ester defoamer, 0.004 parts of BYK-163 high molecular weight block copolymer dispersant containing affinity groups, 0.006 parts of BYK-320 polyether modified methane polysiloxane copolymer leveling agent, and 0.011 parts of TEGOWet270 polyether siloxane copolymer wetting agent to the solution obtained in step 1), stirring at a low speed of 1000 r / min for 5 minutes, and controlling the stirring temperature to be lower than 40° C.;

[0153] 3) adding 0.04 parts of polyamide wax, 0.35 parts of precipitated barium sulfate, 0.58 parts of rutile titanium dioxide, 0.11 parts of colloidal graphite, 0.37 parts of barite, 0.11 parts of ZP-01 composite modified zinc aluminum phosphate, and 0.01 parts of nano-silicon dioxide to the solution obtained in step 2), and stirring at 2500 r / min for 30 minutes, controlling the stirring temperature to be lower than 50° C.;

[0154] 4) Grinding the solution obtained in step 3) with a sand mill for 1.0 h to obtain a coating base liquid, with the grinding fineness being controlled to be ≤60 μm;

[0155] 5) adding 0.95 parts of glass flakes with a diameter of 60 to 80 meshes and 0.05 parts of GRF-FLGOD-04 thin-layer graphene dispersion slurry to the coating base liquid obtained in step 4), stirring at 2000 r / min for 40 minutes, controlling the stirring temperature to be lower than 60° C., to obtain a first composition;

[0156] 6) adding 3.2 parts of DF1228 cardanol modified phenolic amine curing agent, 3.5 parts of Ancamine 2636 modified fatty amine curing agent, and 0.9 parts of DMP-30 curing agent to 0.3315 parts of xylene, 0.1428 parts of n-butanol, and 0.037 parts of ethyl acetate, stirring at 1500 r / min for 20 minutes, and controlling the stirring temperature to be lower than 30° C. to obtain a second composition;

[0157] 7) The component A and the component B are mixed uniformly in a weight ratio of 1:0.23 to obtain a coating composition.

[0158] The properties of the coating composition prepared in Comparative Example 4 were tested, and the results are shown in Table 8.

[0159] Table 8 Properties of the coating composition prepared in Comparative Example 4

[0160]

[0161]

[0162] Comparative Example 5

[0163] Comparative Example 1 is different in that the weight ratio of the first composition to the second composition in Comparative Example 5 is outside the preferred range of 1:0.21-0.25.

[0164] 1) Add 1 part of F51 bisphenol A novolac epoxy resin, 0.2275 parts of xylene, 0.098 parts of n-butanol, 0.0245 parts of ethyl acetate, and 0.1 parts of 1,6-hexanediol diglycidyl ether to 1 part of NPPN-631 phenol novolac epoxy resin, stir at 2000 r / min for 25 minutes, and control the temperature below 50° C.;

[0165] 2) adding 0.015 parts of CK021 polyether ester defoamer, 0.008 parts of BYK-163 high molecular weight block copolymer dispersant containing affinity groups, 0.011 parts of BYK-320 polyether modified methane polysiloxane copolymer leveling agent, and 0.005 parts of TEGOWet270 polyether siloxane copolymer wetting agent to the solution obtained in step 1), stirring at a low speed of 1000 r / min for 5 minutes, and controlling the stirring temperature to be lower than 40° C.;

[0166] 3) adding 0.01 parts of polyamide wax, 0.45 parts of precipitated barium sulfate, 0.38 parts of rutile titanium dioxide, 0.11 parts of colloidal graphite, 0.29 parts of barite, 0.18 parts of ZP-01 composite modified zinc aluminum phosphate, and 0.02 parts of nano-silicon dioxide to the solution obtained in step 2), and stirring at 2500 r / min for 30 minutes, controlling the stirring temperature to be lower than 50° C.;

[0167] 4) Grinding the solution obtained in step 3) with a sand mill for 1.0 h to obtain a coating base liquid, with the grinding fineness being controlled to be ≤60 μm;

[0168] 5) adding 1.05 parts of glass flakes with a diameter of 60 to 80 meshes and 0.05 parts of GRF-FLGOD-04 thin-layer graphene dispersion slurry to the coating base liquid obtained in step 4), stirring at 2000 r / min for 40 minutes, controlling the stirring temperature to be lower than 60° C., to obtain a first composition;

[0169] 6) adding 3 parts of DF1228 cardanol modified phenolic amine curing agent, 3.1 parts of Ancamine 2636 modified fatty amine curing agent, and 0.7 parts of DMP-30 curing agent to 0.3315 parts of xylene, 0.1428 parts of n-butanol, and 0.037 parts of ethyl acetate, stirring at 1500 r / min for 20 minutes, and controlling the stirring temperature to be lower than 30° C. to obtain a second composition;

[0170] 7) The component A and the component B are mixed uniformly in a weight ratio of 1:0.35 to obtain a coating composition.

[0171] The properties of the coating composition prepared in Comparative Example 5 were tested, and the results are shown in Table 9.

[0172] Table 9 Properties of the coating composition prepared in Comparative Example 5

[0173]

[0174]

[0175] Comparative Example 6

[0176] Comparative Example 1 is different in that the parameters of each stirring and grinding step in Comparative Example 6 are outside the preferred range of the present invention.

[0177] 1) Add 1 part of F51 bisphenol A novolac epoxy resin, 0.2275 parts of xylene, 0.098 parts of n-butanol, 0.0245 parts of ethyl acetate, and 0.1 parts of 1,6-hexanediol diglycidyl ether to 1 part of NPPN-631 phenol novolac epoxy resin, stir at 1900 r / min for 15 minutes, and control the temperature below 50° C.;

[0178] 2) adding 0.015 parts of CK021 polyether ester defoamer, 0.008 parts of BYK-163 high molecular weight block copolymer dispersant containing affinity groups, 0.011 parts of BYK-320 polyether modified methane polysiloxane copolymer leveling agent, and 0.005 parts of TEGOWet270 polyether siloxane copolymer wetting agent to the solution obtained in step 1), stirring at a low speed of 800 r / min for 3 minutes, and controlling the stirring temperature to be lower than 40° C.;

[0179] 3) adding 0.01 parts of polyamide wax, 0.45 parts of precipitated barium sulfate, 0.38 parts of rutile titanium dioxide, 0.11 parts of colloidal graphite, 0.29 parts of barite, 0.18 parts of ZP-01 composite modified zinc aluminum phosphate, and 0.02 parts of nano-silicon dioxide to the solution obtained in step 2), and stirring at 1800 r / min for 20 minutes, controlling the stirring temperature to be lower than 50° C.;

[0180] 4) grinding the solution obtained in step 3) with a sand mill for 0.6 h to obtain a coating base liquid;

[0181] 5) adding 1.05 parts of glass flakes with a diameter of 60 to 80 meshes and 0.05 parts of GRF-FLGOD-04 thin-layer graphene dispersion slurry to the coating base liquid obtained in step 4), stirring at a high speed of 1800 r / min for 25 minutes, and controlling the stirring temperature to be lower than 60° C. to obtain a first composition;

[0182] 6) adding 3 parts of DF1228 cardanol modified phenolic amine curing agent, 3.1 parts of Ancamine 2636 modified fatty amine curing agent, and 0.7 parts of DMP-30 curing agent to 0.3315 parts of xylene, 0.1428 parts of n-butanol, and 0.037 parts of ethyl acetate, stirring at 800 r / min for 8 minutes, controlling the stirring temperature to be lower than 30° C., to obtain a second composition;

[0183] 7) The component A and the component B are mixed uniformly in a weight ratio of 1:0.23 to obtain a coating composition.

[0184] The properties of the coating composition prepared in Comparative Example 6 were tested, and the results are shown in Table 10.

[0185] Table 10 Properties of the coating composition prepared in Comparative Example 6

[0186]

[0187] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0188] By comparing Examples 1-4 with Comparative Examples 1-2, it can be seen that in the coating composition of the present invention, by using phenol novolac epoxy resin and bisphenol A novolac epoxy resin as film-forming resins and by using a graphene dispersion, the curing time of the coating is shortened, and the mechanical properties, heat resistance, media resistance, salt spray resistance and chloride ion permeability resistance of the coating are improved.

[0189] Comparing Examples 1-4 with Comparative Example 3, it can be seen that the use of zinc aluminum phosphate in the coating composition of the present invention is beneficial to further improve the media resistance and salt spray resistance of the coating.

[0190] Comparing Examples 1-4 with Comparative Example 4, it can be seen that using each component in the coating composition of the present invention within the specific content range of the present invention is beneficial to further improve the heat resistance, medium resistance and salt spray resistance of the coating.

[0191] Comparing Examples 1-4 with Comparative Example 5, it can be seen that when the weight ratio of the first composition to the second composition is outside the range of 1:0.21 to 0.25, the curability of the coating may decrease.

[0192] Comparing Examples 1-4 with Comparative Example 6, it can be seen that in the method for preparing a coating composition of the present invention, using stirring and grinding parameters within the specific range of the present invention is beneficial to further improve the dispersibility, heat resistance, medium resistance and salt spray resistance of the coating.

[0193] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0194] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A coating composition, characterized in that The coating composition is formed from a first composition and a second composition, The first composition comprises the following components: phenol novolac epoxy resin, bisphenol A novolac epoxy resin, glass flakes, graphene dispersion, other pigments and fillers, a first solvent, a reactive diluent, a thixotropic agent, a defoaming agent, a dispersant, a leveling agent, and a substrate wetting agent; The second composition comprises the following components: a phenalkamine curing agent, an alicyclic amine curing agent, a curing accelerator, and a second solvent.

2. The coating composition according to claim 1, characterized in that The first composition comprises the following components in parts by weight: 1-1.05 parts of phenol novolac epoxy resin, 1-1.2 parts of bisphenol A novolac epoxy resin, 1-1.13 parts of glass flakes, 0.03-0.05 parts of graphene dispersion, 1.53-1.61 parts of other pigments and fillers, 0.35-0.55 parts of the first solvent, 0.08-0.15 parts of the active diluent, 0.01-0.03 parts of the thixotropic agent, 0.012-0.018 parts of the defoaming agent, 0.006-0.008 parts of the dispersant, 0.007-0.011 parts of the leveling agent, and 0.004-0.009 parts of the substrate wetting agent; The second composition comprises the following components in parts by weight: 3 to 3.1 parts of a phenalkamine curing agent, 3.1 to 3.4 parts of an alicyclic amine curing agent, 0.5 to 0.7 parts of a curing accelerator, and 0.50 to 0.65 parts of a second solvent.

3. The coating composition according to claim 1 or 2, characterized in that The phenol novolac epoxy resin is NPPN-631 phenol novolac epoxy resin, and the bisphenol A novolac epoxy resin is F51 bisphenol A novolac epoxy resin; The glass flakes have a diameter of 60 to 80 meshes and a thickness of less than 7 μm; The graphene dispersion is a GRF-FLGOD-04 thin-layer graphene dispersion slurry; The other pigments and fillers include the following components by weight: 0.45-0.59 parts of precipitated barium sulfate, 0.37-0.45 parts of rutile titanium dioxide, 0.11-0.18 parts of colloidal graphite, 0.27-0.38 parts of barite, 0.16-0.19 parts of ZP-01 composite modified zinc aluminum phosphate and 0.01-0.07 parts of nano silicon dioxide; The first solvent comprises the following components in parts by weight: 0.2275-0.3575 parts of xylene, 0.098-0.154 parts of n-butanol, 0.0245-0.0385 parts of ethyl acetate, the second solvent comprising the following components in parts by weight: 0.325-0.4225 parts of xylene, 0.14-0.182 parts of n-butanol, 0.035-0.0455 parts of ethyl acetate; The active diluent is 1,6-hexanediol diglycidyl ether; The thixotropic agent is polyamide wax, the defoamer is CK021 type polyether ester defoamer, the dispersant is BYK-163 type high molecular weight block copolymer dispersant containing affinity groups, the leveling agent is BYK-320 type polyether modified methane polysiloxane copolymer leveling agent, and the substrate wetting agent is TEGO Wet 270 type polyether siloxane copolymer wetting agent; The phenolic amine curing agent is a DF1228 cardanol-modified phenolic amine curing agent, the alicyclic amine curing agent is an Ancamine 2636 modified fatty amine curing agent, and the curing accelerator is a DMP-30 curing agent.

4. The coating composition according to claim 1 or 2, characterized in that The weight ratio of the first composition to the second composition is 1:0.21-0.

25.

5. The coating composition according to claim 4, characterized in that The weight ratio of the first composition to the second composition is 1:0.22-0.

23.

6. A method for preparing the coating composition according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: 1) mixing and stirring the components of the first composition except the glass flakes and the graphene dispersion to obtain a coating mixture; 2) grinding the coating mixture obtained in step 1) to obtain a coating base liquid; 3) adding the glass flakes and the graphene dispersion into the coating base liquid and stirring to obtain the first composition; 4) mixing and stirring the components of the second composition to obtain the second composition; 5) Mixing the first composition and the second composition to obtain the coating composition.

7. The method according to claim 6, characterized in that In step 1), the bisphenol A novolac epoxy resin physically modifies the phenol novolac epoxy resin.

8. The method according to claim 6, characterized in that Step 1) comprises the following steps: i) mixing the phenol novolac epoxy resin, the bisphenol A novolac epoxy resin, the reactive diluent and the first solvent and performing a first stirring to obtain a resin solution, wherein the first stirring temperature is ≤50° C., the rotation speed is 2000-2500 r / min, and the time is 20-25 min; ii) adding the defoamer, the dispersant, the leveling agent, and the substrate wetting agent into the resin solution and performing a second stirring to obtain a resin mixed solution, wherein the second stirring temperature is ≤40° C., the rotation speed is 1000-1500 r / min, and the time is 5-10 min; iii) adding the thixotropic agent and the other pigments and fillers into the resin mixed solution and performing a third stirring, wherein the third stirring temperature is ≤50° C., the rotation speed is 2000-2500 r / min, and the time is 25-30 min.

9. The method according to claim 6, characterized in that The grinding in step 2) is carried out for 1 to 1.5 hours, and the grinding fineness is ≤ 60 μm.

10. The method according to claim 6, characterized in that The stirring temperature in step 3) is ≤60°C, the rotation speed is 2000-2500r / min, and the time is 30-40min; the stirring temperature in step 4) is ≤30°C, the rotation speed is 1000-1500r / min, and the time is 15-20min.

Citation Information

Patent Citations

  • High-solid phenolic aldehyde epoxy glass scale anti-corrosion paint and preparation method thereof

    CN109749585A

  • Anti-corrosion coating for blast furnace gas generator blade as well as preparation method and application of anti-corrosion coating

    CN113292901A

  • Water-based anticorrosive coating composition and anticorrosion method

    JP5296899B1